ANALISA KUALITAS PELAYANAN DAN PENGARUH KINERJA PROFESIONAL TERHADAP KEPUASAN MASYARAKAT PADA KANTOR KECAMATAN TEWEH TENGAH - muhamad Rifai; Listra Hatiokia (Sekolah Tinggi Ilmu Ekonomi Muara Teweh, 2025)
This research aims to evaluate how service quality and employee professionalism influence community satisfaction at the Teweh Tengah District Office. The study applies a quantitative approach with descriptive support from qualitative data. Questionnaires were distributed to 100 respondents from the local community. The results of the partial T-test showed that the t-count of 3.692 was greater than the t-table value of 1.985, with a significance of 0.001, which means there is a significant partial effect on community satisfaction. Conversely, another partial T-test showed a t-count of -0.844, smaller than the t-table 1.985 with a significance of 0.401, indicating no partial effect. The simultaneous F-test showed a calculated value of 7.105, greater than the f-table value of 3.09, with a significance of less than 0.001, which indicates a significant combined effect. Service quality (X1) and professional performance (X2) have Standardized Coefficients Beta of -0.097 and 0.209, with the RÂ² Determination Coefficient test resulting in 12.8%